2015
DOI: 10.1007/s12160-015-9741-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Behavioral Self-Regulation Intervention on Patient Adherence to Fluid-Intake Restrictions in Hemodialysis: a Randomized Controlled Trial

Abstract: The present study found that participation in a behavioral self-regulation intervention resulted in no unique intervention effect on a key indicator of adherence for those with severe chronic kidney disease. There was, however, modest within-subjects improvement in interdialytic weight gain for the intervention group which meshes with other evidence showing the utility of behavioral interventions in this patient population. ClinicalTrials.gov Identifier: NCT01066949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 50 publications
(48 reference statements)
2
55
0
7
Order By: Relevance
“…Twenty-four potentially relevant studies were identified for full-text analysis, but 2 were excluded for low quality, 13 were excluded because of a lack of key data for analysis. Finally, 9 RCT studies were selected, 6 published in English [10, 12-14, 23-24] and 3 in Chinese [25-27]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four potentially relevant studies were identified for full-text analysis, but 2 were excluded for low quality, 13 were excluded because of a lack of key data for analysis. Finally, 9 RCT studies were selected, 6 published in English [10, 12-14, 23-24] and 3 in Chinese [25-27]. …”
Section: Resultsmentioning
confidence: 99%
“…Such interventions, including education, training, and behavioral introduction, which help patients gain more knowledge of dialysis and develop healthy life habits, further improve their compliance with this treatment [3, 10-13]. To date, the most commonly reported indicators for the assessment of compliance include serum phosphorus level and interdialytic weight gain (IDWG), whereas in some studies compliance has been directly evaluated and the compliance rate reported [12-14]. Recently, guidelines for compliance have been established by the World Health Organization and the National Kidney Foundation Dialysis Outcome and Quality Initiative (KDOQI) [8, 15-17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HD'de en fazla stres yaratan ve tedaviye uyumda zorlanılan alan sıvı kısıtlamasıdır (4,19,21,22,23,24,25). Hastalık ilerledikçe HD hastaları idrar oluşturma yeteneklerini kaybeder.…”
unclassified